2013
DOI: 10.1021/am402083n
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Surface Site Activation: A Rate Limiting Process in Electron Beam Induced Etching

Abstract: We report a new mechanism that limits the rate of electron beam induced etching (EBIE). Typically, the etch rate is assumed to scale directly with the precursor adsorbate dissociation rate. Here, we show that this is a special case, and that the rate can instead be limited by the concentration of active sites at the surface. Novel etch kinetics are expected if surface sites are activated during EBIE, and observed experimentally using the electron sensitive material ultra nanocrystalline diamond (UNCD). In prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 50 publications
3
44
0
Order By: Relevance
“…The technique is analogous to focused ion beam processing [6][7][8][9][10][11], but avoids damage, staining and redeposition artifacts caused by ion bombardment. EBIE is realized using gaseous precursors such as H 2 O, O 2 , NH 3 , XeF 2 , Cl 2 and SF 6 , which have been used to volatilize a wide range of materials, including graphene [12], single [13] and multi-walled [14] C nanotubes, amorphous carbon [15][16][17][18], single crystal [19][20][21][22] and nano-crystalline [23] diamond, Si, SiO 2 , Si 3 N 4 , Cr, Ti, TaN and photoresist [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Historical overviews and reviews of the EBIE technique and the underlying chemical pathways can be found in references [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The technique is analogous to focused ion beam processing [6][7][8][9][10][11], but avoids damage, staining and redeposition artifacts caused by ion bombardment. EBIE is realized using gaseous precursors such as H 2 O, O 2 , NH 3 , XeF 2 , Cl 2 and SF 6 , which have been used to volatilize a wide range of materials, including graphene [12], single [13] and multi-walled [14] C nanotubes, amorphous carbon [15][16][17][18], single crystal [19][20][21][22] and nano-crystalline [23] diamond, Si, SiO 2 , Si 3 N 4 , Cr, Ti, TaN and photoresist [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Historical overviews and reviews of the EBIE technique and the underlying chemical pathways can be found in references [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Chemically active surface regions have previously been used as catalytic templates for electron beam directed, room temperature chemical vapor deposition, [1][2][3] and to locally accelerate the etch rate of diamond. 4 Here we present a beam-directed chemical technique for controlling the charge states of luminescence centers in semiconductors. The diamond NV center, comprised of a substitutional nitrogen atom adjacent to a carbon vacancy, is the subject of intense research into qubits for use in quantum computing, 5 markers for live cell imaging, fields.…”
mentioning
confidence: 99%
“…The UNCD substrates were ⇠ 1.7 µm films grown on silicon by hot filament chemical vapor 23,36 . The eCell shown in Fig.…”
Section: (B)mentioning
confidence: 99%
“…because it improves the degree of control over the vacuum chamber environment 25,38 , and enables EBIE experiments to be performed with a high degree of reproducibility 23 . Two liquid nitrogen (LN) cold traps were installed, one on a gas delivery line and one inside the eCell (see Fig.…”
Section: (B)mentioning
confidence: 99%
See 1 more Smart Citation